2008
DOI: 10.1373/clinchem.2007.097998
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactivity of BNP, NT-proBNP, and proBNP in Commercial BNP and NT-proBNP Assays: Preliminary Observations from the IFCC Committee for Standardization of Markers of Cardiac Damage

Abstract: B-type natriuretic peptide (BNP) is a 32 amino acid cardiacsynthesized hormone that reduces blood pressure and increases sodium excretion (1 ). Following proteolytic cleavage of proBNP, a 108-amino acid precursor, an Nterminal fragment (NT-proBNP) and BNP are released (2 ). Increased concentrations of BNP and NT-proBNP can be used clinically to monitor heart failure, but a lack of alignment between commercial BNP and NT-proBNP assays (3 ) can lead to confusion when clinicians or laboratorians compare results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 5 publications
3
103
0
2
Order By: Relevance
“…However, values are assay-specific with limited comparability (11,12). In addition, cross-reactivity with pro-BNP, the precursor form with six-to eightfold lower biological activity, and glycosylated forms of BNP has been demonstrated (13). This is of particular importance as patients with heart failure have evidence of increased levels of circulating pro-hormone (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…However, values are assay-specific with limited comparability (11,12). In addition, cross-reactivity with pro-BNP, the precursor form with six-to eightfold lower biological activity, and glycosylated forms of BNP has been demonstrated (13). This is of particular importance as patients with heart failure have evidence of increased levels of circulating pro-hormone (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is extensive variation depending upon the nature of the natriuretic peptide calibrators used and their glycosylation ( Table 2). Cross-reactivity of BNP with proBNP was also demonstrated; this is particularly important in HF patients since proBNP is more prevalent in these patients (36 ). A summary of crossreactivity of BNP and NT-proBNP assays currently in clinical use is presented in Fig.…”
Section: Analytics Of Natriuretic Peptide Assaysmentioning
confidence: 95%
“…Moreover, a recent study [34] suggested that the commercial immunoassays, commonly used for NTproBNP assay, employ non-glycosylated calibrator materials and mostly antibodies directed against epitopes with potential O-glycosylation site occupancy. Because the most part of circulating inactive peptides related to NT-proBNP and proBNP are O-glycosylated [7,18,35], these immunoassays cannot measure some glycosylated peptides [34,36]. Moreover, the commercially available immunoassays for NT-proBNP are interfered by the intact peptide proBNP (especially non-glycosylated peptide) [36] and also by some other shorter peptides derived from the proteolytic degradation of this pro-hormone [1] (Figure 2).…”
Section: Groupmentioning
confidence: 99%
“…Because the most part of circulating inactive peptides related to NT-proBNP and proBNP are O-glycosylated [7,18,35], these immunoassays cannot measure some glycosylated peptides [34,36]. Moreover, the commercially available immunoassays for NT-proBNP are interfered by the intact peptide proBNP (especially non-glycosylated peptide) [36] and also by some other shorter peptides derived from the proteolytic degradation of this pro-hormone [1] (Figure 2). In conclusion, the commercially available immunoassays for NT-proBNP do not allow an accurate measurement of this peptide.…”
Section: Groupmentioning
confidence: 99%
See 1 more Smart Citation